2015
DOI: 10.1016/j.jdmm.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

SoCoMo marketing for travel and tourism: Empowering co-creation of value

Abstract: Context-based marketing has gained significant attention as advanced technology enables users to amalgamate information from various sources on their mobile devices, personalise their profile through applications and social networks as well as interact dynamically with their context. The information overload, caused by the extreme amount of information available online, has generated a need for more context-relevant information. Tourism marketers are increasingly becoming aware of those cutting-edge Informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
289
1
21

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(317 citation statements)
references
References 49 publications
6
289
1
21
Order By: Relevance
“…The generation of insights for new products and services was cited as value creation in 10 papers, representing 58.82% of the total being (Buhalis and Foerste, 2015;Zhou et al, 2015;Chang et al, 2015;Acito and Khatri, 2014;Opresnik and Taisch, 2015;Erevelles et al, 2015;Ziora, 2015;Akter and Wamba, 2016;Mezaour et al, 2014;Fawcett and Waller, 2014). Regarding the cost reduction, it was found that four papers were related to value creation, which represent 23.54% of the total.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of insights for new products and services was cited as value creation in 10 papers, representing 58.82% of the total being (Buhalis and Foerste, 2015;Zhou et al, 2015;Chang et al, 2015;Acito and Khatri, 2014;Opresnik and Taisch, 2015;Erevelles et al, 2015;Ziora, 2015;Akter and Wamba, 2016;Mezaour et al, 2014;Fawcett and Waller, 2014). Regarding the cost reduction, it was found that four papers were related to value creation, which represent 23.54% of the total.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Buhalis and Foerste (2015), for example, say that destination management organizations could revolutionize their o®erings to co-create products and dynamic services to their customers, being the way value is created in their context. Marketing-based actions would seek to dynamically engage users in cocreation through their experiences and based on the optimization of internal and external conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Takođe, Internet se u velikoj meri koristi i kao promotivno sredstvo [8,9]. Savremeni turisti su u potpunosti prihvatili korišćenje online alata i može se reći da je, u transakcijama povezanim sa putovanjima, uloga Interneta dostigla svoj vrhunac [10].…”
Section: Smart Turizamunclassified
“…For instance, new technologies can be used for context-based marketing in order to recognize the physical environment of their customers (Buhalis and Foerste, 2015). In addition Sigala et al (2012) or Ge et al (2013) emphasize the relevance of social media in tourism or its use to achieve strategic marketing goals.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of big data from customer social media interaction can be used to extend the customer profile and provide personalized services (Buhalis and Foerste, 2015). A recent study in Spanish hotels pointed out that tourism companies should integrate IT in their marketing to enhance the relation between hotels, service distributors, and travel agencies (Moliner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%